Gamification strategy to support self-directed learning in an online learning environment - Palaniappan, Kavitha (International Association of Online Engineering, 2022)
This research measures the effect of gamification on learners’ academic performance, investigate their self-directed learning level within an online gamification learning environment and identify the relationship between learners self-directed learning level and their gamification learning experience. Pre-experimental research (single group) was carried out for a duration of 5 weeks among a group of 29 undergraduate year 2 learners froma non-major computer science course undertaking basic programming language subject. The learners SDL and knowledge on the subject was measured with a questionnaire and assessment test before and after the gamification learning intervention. A gamification experience questionnaire was used to evaluate their gamification learning experience after the intervention. The learning environment was infused with gamification in the form of competition to earn points, leaderboard ranks and python programmer badge. The learner’s academic performance has significantly improved (p=0.000 < 0.05) after the gamification injection. Leaners selfdirected learning level also increased and there is a significant difference before (M=3.59) and after (M=4.22) the gamification strategy (p=0.000 < 0.05) imposed. Self-management, motivation and self-monitoring were all at high level with significance before and after (p=0.000 < 0.05) the gamified learning activities. Overall, the gamification strategy used in the online learning environment shows a positive influence to support learner’s self-directed learning.